2001
DOI: 10.1536/jhj.42.451
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of T-Wave Alternans and QT interval Dispersion to Predict Ventricular Tachyarrhythmia in Patients with Dilated Cardiomyopathy and without Antiarrhythmic Drugs.

Abstract: SUMMARYMicrovolt T-wave alternans (TWA) and QT interval dispersion (QTD), which reflect temporal and spatial repolarization abnormalities, respectively, have been proposed as useful indices to identify patients at risk for ventricular tachyarrhythmias (VTs). The purpose of this study was to clarify which repolarization abnormality marker is more useful in predicting arrhythmic events in patients with dilated cardiomyopathy (DCM).Forty-two consecutive nonischemic DCM patients underwent the assessment of TWA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…45,51,52 Several recent studies have found no relation between QT dispersion and outcome. 24,46,[53][54][55] Lack of a clear physiological correlate further clouds the utility of this parameter.…”
Section: Qt Interval and Qt Dispersionmentioning
confidence: 99%
“…45,51,52 Several recent studies have found no relation between QT dispersion and outcome. 24,46,[53][54][55] Lack of a clear physiological correlate further clouds the utility of this parameter.…”
Section: Qt Interval and Qt Dispersionmentioning
confidence: 99%
“…Therefore, MTWA has been proposed as a new noninvasive tool for stratification of patients at high risk of SCD and ventricular arrhythmias in CHF patients with ischemic or nonischemic cardiomyopathy [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The results of several studies [15][16][17][18][19][20][21][22]30,31] demonstrated that MTWA is a promising predictor of SCD or major arrhythmic events in patients with DCM.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical and experimental studies [12][13][14] have shown that MTWA is strictly correlated with presence of inducible and spontaneous ventricular tachycardia/fibrillation (VT/VF). Therefore, MTWA has been proposed as a new non-invasive tool for stratification of patients with DCM at high risk of SCD and malignant arrhythmias [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%